A conceitualização dos números irracionais no primeiro ano do Ensino Médio - Santos, Josimar José dos (2014)
This research aim to present a proposal of activities (didactic proposal) directed to the conceptualization of irrational numbers in the 1st year of High School. The choice related to the concept of the irrational number as the main element of the current work has been done because of the non-importance assigned to the teaching and the conceptualization of irrational numbers in the basic education. This current work has the book Número Irracionais e Transcedentes de Figueiredo (2002) and the Pommer’s master thesis dissertation (2012) as the main source. The methodological procedure of the current research are focused on the didactic proposal in three topics: irrationality via decimal representation of the real numbers, irrationality of √2 and the π p irrationality.